ANALISIS PRODUKSI KOPI DI KECAMATAN DAMPIT KABUPATEN MALANG - Indri Retno Cahyani; Wahyu Hidayat; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2018)
This study aims to analyze the effect of land area, labor, production cost of production to Sridonoretno coffee production in Kecamatan Dampit Malang Regency in one season. The data used is primary data, primary data obtained through field interview directly to 54 coffee farmers. The method in this research is quantitative. The model consists of independent and dependent variables, where the independent variable consists of land area, labor and production cost. While the dependent variable is the result of coffee production. Based on multiple linear regression analysis showed that land area (0.217061) and production cost (1.048386) have a positive and significant effect on coffee production. While labor (-0.080136) have a significant negative effect on coffee production. Hypothesis test shows the coefficient of determination (R2) value is 0.999521 and the value of the probability of F-statistic test is significant at α 5%.Keywords:productions results, land area, labor, cost